IMPROVING THE MECHANISMS OF ORGANIZATION AND MANAGEMENT OF EDUCATIONAL RELATIONS PROCESSES IN HIGHER EDUCATION INSTITUTIONS - Farhodov Fozilbek Bahrom ugli; Turgunov Sobitkhan Toshpolatovich (American Journals, 2023)
One of the urgent problems is to organize and manage the activities of future personnel in the higher education system in order to master modern knowledge, become the owner of high culture, reach high peaks in their activities, and educate young people who are responsible for the country's destiny and future. This article discusses this issue.
Keywords: Teacher, management, education, methodology, pedagogy, education.